“Alexa, You're Really Stupid”: A Longitudinal Field Study on Communication Breakdowns Between Family Members and a Voice Assistant - Mavrina, Lina; Szczuka, Jessica; Strathmann, Clara; Bohnenkamp, Lisa Michelle; Krämer, Nicole; Kopp, Stefan (Frontiers in Computer Science, 2022)
We present the results of our long-term study on use of a voice assistant (Amazon Alexa via Echo Dot) in nine families with children and no previous experience with this technology. The study was conducted over the course of five weeks during which the families could interact with the device freely. Three house visits were made to collect empirical data from the adult participants in form of questionnaires. Additionally, conversational data from log files of the voice assistant were obtained. These data were annotated and analysed with a focus on communication breakdowns. We investigate user behaviour for adults and children in such situations, its reasons and consequences for user satisfaction. This article provides qualitative analysis of three interesting breakdown cases, as well as statistical analysis regarding several research questions combining empirical and conversational data. Described cases of communication breakdown illustrate findings from existing literature. The statistical analysis paints a mixed picture, however, it helped us identify further avenues for research, some of which can be explored with our data set. We found a significant negative effect of the number of abandoned failed requests on user satisfaction, contrary to the number of successfully repaired requests that had no impact. We discovered that users are more inclined to use reformulation as repair strategy when they do not perceive miscommunication as their fault. We could not identify a significant effect of internal reasons for the choice of other strategies, so we suggest that situational clues such as the immediate response of the voice assistant are more important for the choice of repair strategy. Our results also hint that users distinguish between repair strategies differently, as the self-perceived frequency of repetitions and abortions of requests were found to be positive predictors for the use of reformulation-based strategies. With regards to the long-term aspect of the study, use of repetitions as a repair strategy by both children and adults significantly decreased with time, no other changes were found for other strategies. Additionally, no significant impact of age on the choice of repair strategy was found, as well as no interaction effect between age and time.